NEUROSCIENCE AS A TOOL FOR SELF-KNOWLEDGE AND DEVELOPMENT OF COGNITIVE POTENTIAL FOR PEOPLE IN VULNERABLE SITUATIONS - da Silva, Renata Godis (Seven Editora, 2025)
This work, conducted at the Institute for Socio-Emotional Development of the State of Rio de Janeiro, uses neuroscience as an analysis to understand mental obstacles that hinder the development of cognitive potential crucial for overcoming emotional barriers. These barriers often prevent vulnerable individuals from achieving the life they desire. To contribute to overcoming personal difficulties, this work aims to offer tools to enable a group of people in Rio de Janeiro to develop their self-awareness and move beyond their psychic comfort zones, encouraging reflection on paradigms created through lived experiences and motivating personal transformation. Neuroscience has provided vast insights into mental organization, and awakening minds to their full potential has never been more widely discussed than in the current decade. Thus, the possibilities for overcoming these challenges reaffirm the importance of rethinking proposals that foster a new perspective and new social outlook for this group of individuals. DOI: https://doi.org/10.56238/sevened2025.038-049